Diagnostic Accuracy of CT Scan Abdomen in Differentiating Peritoneal Tuberculosis from Peritoneal Carcinomatosis, Taking Omental Biopsy as Gold Standard - Anjum, Asfa; Pasha, Nazahat (Biological and Clinical Sciences Research Journal, 2025)
Peritoneal tuberculosis (PTB) and peritoneal carcinomatosis (PC) often present with overlapping clinical and radiological features, making differentiation challenging. In tuberculosis-endemic regions such as Pakistan, accurate non-invasive diagnosis is vital to guide appropriate treatment and avoid mismanagement. Objective: To assess the diagnostic accuracy of contrast-enhanced CT (CECT) in differentiating peritoneal tuberculosis from peritoneal carcinomatosis using omental biopsy as the gold standard. Methods: This cross-sectional analytical study was conducted at the Department of Radiology, Chaudhry Pervaiz Elahi Institute of Cardiology (CPEIC), Multan, over a period of six months from April 2024 to September 2024. A total of 149 patients aged 30–65 years with suspected peritoneal disease were included. All participants underwent CECT followed by omental biopsy. CT findings were compared with histopathology. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy were calculated using SPSS version 25. Results: CT scan showed a sensitivity of 90.4%, specificity of 80.3%, PPV of 85.2%, NPV of 86.9%, and an overall diagnostic accuracy of 85.9%. Further stratified analysis revealed consistent diagnostic performance across age, gender, and residential status, supporting the modality’s reliability in diverse subpopulations. Conclusion: CT scan is a reliable, non-invasive diagnostic tool for distinguishing PTB from PC, especially in TB-endemic settings like Pakistan. While omental biopsy remains the definitive diagnostic method, CT can play a pivotal role in guiding clinical decisions and reducing diagnostic delays.